Judicial Considerations on Children's Rights Fulfillment in Divorce Rulings: A Study at Makassar Class 1A Religious Court - Karmawati, Karmawati; Kurniati, Kurniati; Asni, Asni; Syafii, Ahmad (Fakultas Syariah Institut Agama Islam Negeri Palu, 2025)
The rising divorce rate in Makassar City has significantly impacted children's psychological well-being and educational rights. This study aims to analyze the judicial considerations of judges at the Makassar Class 1A Religious Court regarding the fulfillment of children's rights in divorce rulings, viewed through the perspective of Maqasid al-Syari'ah. This research employs a qualitative method with a field study design, utilizing data from verdict analysis and interviews with judges. The findings indicate that judges prioritize the child's primary interests (maslahat primer), covering the protection of life (hifz al-nafs) and intellect (hifz al-’aql). Judges implement progressive policies, such as mandating an annual percentage increase in child support (e.g., 10%) to combat inflation and determining custody based on the parent's moral and educational assurance rather than strict age limits. However, the effectiveness of these rulings is hindered by the Indonesian Civil Procedure Law, which lacks an automatic monitoring mechanism, often rendering child support rulings as